Hypothyroidism and its relationship to cholesterol levels in premenopausal women: A cross-sectional study - Sahar Mudassar, Mudassar Ali, Faheem Mahmood, Farukh Bashir, Shoaib Ahmed, Amna Mubeen, Amal Shaukat (Pakistan Journal of Medical & Health Sciences, 2022)
Background: A brief overview of the disease: Thyroid dysfunction is a common premenopausal ailment characterized by subtle signs and symptoms that may go unnoticed for a lengthy period of time. Female hypothyroidism is common in the older population. In patients with SCH, primary hypothyroidism is a prevalent consequence. Aim: To determine the prevalence of thyroid dysfunction and the associated clinical symptoms in premenopausal women who attended gynecology outpatient appointments. Methods: The purpose of this study was to determine the prevalence of thyroid dysfunction and its associated clinical symptoms in premenopausal women who were seen as outpatients in gynecology. The participants in this research ranged in age from 42 to 52 years. Thyroid function and blood cholesterol were measured in all of the SCH patients using an ELISA assay. Results: Seventy women between the ages of 42 and 52 participated in the research. Patients with menorrhagia accounted for 56% of all cases of menstrual disturbance in the study population. Women who experienced oligomenorrhea, a premenopausal symptom, accounted for 40% of the total. Thyroid impairment was shown to be associated with irregular menstruation (80% of cases) and weight gain (80 %). irritability and mood fluctuations (59 %) are common (70 %) Anxiety and depression are the most prevalent symptoms (58 %), followed by the loss of one's job. astonishment (6 % ) TSH levels were elevated in SCHs, while free T3 and T4 levels remained normal. There were 17 with SCH, 4 with hypothyroidism, and 49 with normal thyroid function. Seventy percent of individuals with SCH had hypercholesterolemia. Conclusion: Our findings encourage regular screening of premenopausal women, regardless of whether or not they are experiencing symptoms. Early detection and treatment of issues can help to avoid difficulties.